1982
DOI: 10.1111/j.1439-0310.1982.tb00492.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Function of Scent Marking in Territories

Abstract: The energetic costs and the risk of injury in agonistic encounters can be reduced by prior assessment of opponents: it will generally pay low quality animals to avoid combat with one of high quality. Following this principle it is suggested that territory owners scent mark their territories to provide intruders with a means of assessment. When the odour of a competitor, or of a mark it is seen to have made, matches that of scent marks encountered in the vicinity, then the competitor is probably the territory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
275
2
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(289 citation statements)
references
References 64 publications
11
275
2
1
Order By: Relevance
“…Sun and Müller-Schwarze (1998b) showed that beavers' response to AGS from unfamiliar adult males remained at about the same level, but their response to castoreum showed a descending trend. The descending trend in response to the same signal without matching the signaler demonstrates a declining importance of the signal over time, i.e., the scent-matching hypothesis (Gosling, 1982) was supported. The scent-matching hypothesis predicts, among other things, that the territory owner should make itself available for scent matching by the intruder (Gosling, 1982).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Sun and Müller-Schwarze (1998b) showed that beavers' response to AGS from unfamiliar adult males remained at about the same level, but their response to castoreum showed a descending trend. The descending trend in response to the same signal without matching the signaler demonstrates a declining importance of the signal over time, i.e., the scent-matching hypothesis (Gosling, 1982) was supported. The scent-matching hypothesis predicts, among other things, that the territory owner should make itself available for scent matching by the intruder (Gosling, 1982).…”
Section: Discussionmentioning
confidence: 81%
“…The descending trend in response to the same signal without matching the signaler demonstrates a declining importance of the signal over time, i.e., the scent-matching hypothesis (Gosling, 1982) was supported. The scent-matching hypothesis predicts, among other things, that the territory owner should make itself available for scent matching by the intruder (Gosling, 1982). Sun and Müller-Schwarze (1998a) recently documented that related individuals shared more features in the chemical AGS profile than did unrelated individuals, and Sun and Müller-Schwarze (1998c) also demonstrated that it is possible to use some AGS compounds to classify different families.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…If the smells match, then the animal that the intruder has met must be the territory owner. If the hypothesis were true, one would expect owners to (1) mark where intruders are most likely to encounter marks; (2) mark themselves with the substances used to mark the territory; (3) make themselves available for scent matching by intruders; and (4) remove or replace marks of others (Gosling, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Given the constraints of time and energy, scent marks should not be deployed at random, but instead in an organized pattern that maximizes their chance of being 4 discovered by the individuals to whom they are directed, to give the earliest possible warning to a potential trespasser. Such a place might be territorial borders (Gosling, 1982;Gorman, 1990), and the upstream edge of the territory should be most frequently marked if the movement of dispersing individuals is predominantly downstream. The pay-off to the owner is the reduced costs of competition (Gosling, 1986;Gosling and Mckay, 1990).…”
mentioning
confidence: 99%